Implementasi Parameter Sistem Pentanahan Generator Melalui Transformator Distribusi Menggunakan Labview - Ayu Fitriani; Muhammad Fadlan Siregar; Syafriwel; Syofyan Anwar Syahputra (Journal of Informatics, Electrical and Electronics Engineering, 2022)
Determination of the generator neutral grounding system through a distribution transformer can be done through manual calculations. Many parameters are considered in the calculation to get the appropriate results there is the possibility of repeated calculations. This is very difficult and causes a large difference in the calculation results. Therefore, a computer-based computing system is needed to overcome this kind of problem. Several papers have developed the calculation of the required generator neutral earthing magnitude which considers the voltage level, short-circuit fault current and protection system against ground faults. This paper discusses modeling in designing generator neutral ground using the LabView Graphical User Interface (GUI) application. The goal is to be easier, faster and more accurate. As the implementation of the modeling used data from std C62.92.2TM-2017.